2021
DOI: 10.1364/boe.420724
|View full text |Cite
|
Sign up to set email alerts
|

Multi-spectral intravascular photoacoustic/ultrasound/optical coherence tomography tri-modality system with a fully-integrated 0.9-mm full field-of-view catheter for plaque vulnerability imaging

Abstract: Myocardial infarctions are most often caused by the so-called vulnerable plaques, usually featured as non-obstructive lesions with a lipid-rich necrotic core, thin-cap fibroatheroma, and large plaque size. The identification and quantification of these characteristics are the keys to evaluate plaque vulnerability. However, single modality intravascular methods, such as intravascular ultrasound, optical coherence tomography and photoacoustic, can hardly achieve all the comprehensive information to satisfy clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Integrating PA imaging with other contemporary imaging modalities would provide more comprehensive assessments; this benefit will speed up clinical translation. Dai et al [144] and Leng et al [145] reported a trimodality intravascular imaging system which combined PA, US, and OCT for the characterization of atherosclerosis. The addition of OCT contributes to the identification of thin fibrous caps.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating PA imaging with other contemporary imaging modalities would provide more comprehensive assessments; this benefit will speed up clinical translation. Dai et al [144] and Leng et al [145] reported a trimodality intravascular imaging system which combined PA, US, and OCT for the characterization of atherosclerosis. The addition of OCT contributes to the identification of thin fibrous caps.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo imaging capability of the catheter was demonstrated in animal samples. Moreover, for a more comprehensive assessment of intravascular disease, the design of complementary catheters for multimodal imaging has great clinical potential [ 66 ].…”
Section: Research Progress and Applications Of Laser Technology In Intravascular Imaging And Treatmentmentioning
confidence: 99%
“…In this catheter, the low-frequency transducer enhances photoacoustic sensitivity and the high frequency transducer maintains spatial resolution for ultrasound imaging [ 104 ]. In addition, Leng et al demonstrated a novel tri-modality imaging system that can achieve 3D intravascular imaging through a 0.9-mm miniature catheter [ 66 ].…”
Section: Research Progress and Applications Of Laser Technology In Intravascular Imaging And Treatmentmentioning
confidence: 99%
“…32,218 In the near future, multimodal endoscopic OCT will demonstrate significant potential to unleash the full capability of accessing complementary morpho-functional and/or morpho-molecular tissue information needed for improved clinical diagnosis and therapy monitoring. For example, reports on a probe combining OCT and fluorescence imaging 219 providing additional molecular contrast and on a probe combining OCT, PAI, and US 220 have been published. There are still challenges to be solved for a multimodal endoscopic OCT combination: the optic design needs to combine and find the best solution to fulfill the various optical requirements coming from the different image technologies in the scope of limited physical space within an endoscope.…”
Section: Multimodal Endoscopic Oct: More Comprehensive Access To Internal Body Organsmentioning
confidence: 99%